2014
DOI: 10.1292/jvms.13-0455
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Artesunate, Chloroquine, Doxycycline, Primaquine and a Combination of Artesunate and Primaquine against Avian Malaria in Broilers

Abstract: The efficacy of 5 antimalarial drugs was evaluated on P. gallinaceum infected broilers. One hundred and forty-seven 19-day-old broilers were divided into 7 groups of 21 chicks each. Group 1 was the unmedicated, uninfected control. Groups 2–6 were infected and medicated with artesunate, chloroquine, doxycycline, primaquine and an artesunate-primaquine combination, respectively. Group 7 was the unmedicated, infected control. Infectivity, mortality, parasitemia, schizonts in tissues and body weight gain were moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Studies have been carried out to ascertain the efficacy of doxycycline but, despite exhibiting some prophylactic effects [36], its efficacy in avian malaria therapy has not been proven to be significant [15,36,37]. Additionally, doxycycline is a broad-spectrum antibiotic, and its use should be limited to specific clinical needs to avoid the selection of resistant organisms [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been carried out to ascertain the efficacy of doxycycline but, despite exhibiting some prophylactic effects [36], its efficacy in avian malaria therapy has not been proven to be significant [15,36,37]. Additionally, doxycycline is a broad-spectrum antibiotic, and its use should be limited to specific clinical needs to avoid the selection of resistant organisms [38].…”
Section: Discussionmentioning
confidence: 99%
“…infection in birds and the potentially deleterious effects it may generate in hosts, little knowledge about treatments is available to date. Some studies on chickens infected by Plasmodium gallinaceum have described a transient efficacy of chloroquine and doxycycline on the asexual erythrocyte stage, while artesunate and its combination with primaquine were found to be less effective [15]. The combination of atovaquone (AV) and proguanil hydrochloride (PH), commercially known as Malarone ® , was administered in experimentally infected chaffinches (Fringilla coelebs) and greenfinches (Carduelis chloris), effecting recovery from infection but a relapse 43 days after treatment [16].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for Plasmodium species infections of chicken is still limited in commercially available or approved malaria drugs. Though, some medicines such as chloroquine and doxycycline (Sohsuebngarm et al, 2014), or artesunate and tafenoquine (Tasai et al, 2017) showed effectiveness in reduce parasitemia and transmission experimentally. Exo-erythrocytic states of the parasites can lead to persistent parasitemia and relapse, which also make the successfulness of treatment varied between cases and flocks.…”
Section: Treatmentmentioning
confidence: 99%